2011
DOI: 10.1177/1947601911412375
|View full text |Cite
|
Sign up to set email alerts
|

Ranpirnase Interferes with NF- B Pathway and MMP9 Activity, Inhibiting Malignant Mesothelioma Cell Invasiveness and Xenograft Growth

Abstract: The ribonuclease ranpirnase (Onconase) has been used empirically to treat malignant mesothelioma (MM) patients, and some of them had prolonged survivals. The aim of this study was to investigate the mechanisms of the therapeutic function of ranpirnase in MM cells. The effects of ranpirnase were studied in vivo and in vitro on 2 MM cell lines (epithelioid REN and sarcomatoid PPM-Mill). We found that ranpirnase was able to inhibit NF-κB nuclear translocation, evaluated by cell fractionation and immunoblotting as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…These data provide evidence that MSLN promotes MMP secretion contributing to tumor aggressiveness. A recent report further highlights the role of MMP-9-mediated invasion in MPM and the beneficial therapeutic efficacy of suppressing MMP-9 expression(42). In addition to MMP-9, we have observed increased in vitro secretion of MMP 1, 2, and 7 with MSLN overexpression – consistent with published observations that in promoting cancer cell invasion MMPs can influence each other directly(41, 43).…”
Section: Discussionmentioning
confidence: 99%
“…These data provide evidence that MSLN promotes MMP secretion contributing to tumor aggressiveness. A recent report further highlights the role of MMP-9-mediated invasion in MPM and the beneficial therapeutic efficacy of suppressing MMP-9 expression(42). In addition to MMP-9, we have observed increased in vitro secretion of MMP 1, 2, and 7 with MSLN overexpression – consistent with published observations that in promoting cancer cell invasion MMPs can influence each other directly(41, 43).…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been reported previously that ONC is a potent inhibitor of TNF-a dependent NF-κB activity in MM cells. 5 ONC inhibited NF-κB activity and MMP9 secretion, which induced apoptosis in MM cells and decreased MM invasion. 5 Moreover, it was found that ONC inhibited MM tumor growth in a severe combined immunodeficiency (SCID) xenograft mouse model.…”
Section: Introductionmentioning
confidence: 98%
“…5 ONC inhibited NF-κB activity and MMP9 secretion, which induced apoptosis in MM cells and decreased MM invasion. 5 Moreover, it was found that ONC inhibited MM tumor growth in a severe combined immunodeficiency (SCID) xenograft mouse model. 5 These unique mechanisms of action of ONC together with a lack of immunogenicity make ONC a promising alternative to current chemotherapies for MM therapy.…”
Section: Introductionmentioning
confidence: 98%
“…1). Ranpirnase is the smallest member of the ribonuclease (RNase A) superfamily, and appears to be a promising drug with broad clinical application in tumor treatment due to its moderate cytotoxicity, unique synergy, low immunogenicity and few side effects (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Between 1996 and 2004, Tamir Biotechnology, Inc. (formerly Alfacell Corporation) successively conducted clinical investigations regarding the effects of ranpirnase on breast cancer, pancreatic cancer, renal cell carcinoma, non-small cell lung cancer and malignant mesothelioma, for which the therapeutic effect was the most significant with few side effects.…”
Section: Introductionmentioning
confidence: 99%